When Double Intention Ignored: A Study of Corruption Judicial Decisions - Muhammad Arif Setiawan; Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2021)
This study aims to analyze the application of participating perpetrator in court decisions in corruption cases. The research question is whether the double intention as a condition for participating perpetrator in the decision of a corruption case is fulfilled? As a normative legal research, the study in this research is focused on the ratio of four decisions on corruption cases, especially the concept of criminal participation. The results of the study concluded that the double-intentional evidence as a condition for participating perpetrator so was ignored by the panel of judges. The role of involvement of each defendant in the offense of participating perpetrator in the ongoing decision is not described. The judge is not even able to distinguish between the conditions of a person as a perpetrator and the participating perpetrator. In the decisions studied, the judges also mixed the concepts of ordering, advocating, and participating in committing criminal acts of corruption. The judge's inaccuracy in the use of double intention resulted in the emergence of an unfair sentence. Therefore, this study suggests that the Supreme Court should make guidelines for the application of participating perpetrator in corruption cases.